AB0464 EFFECTIVENESS AND SAFETY OF ABATACEPT FOR 24 MONTHS FOR TREATING PATIENTS WITH PRIMARY SJOGREN'S SYNDROME (PSS). (June 2019) - Machado, Adriana; Moça Trevisani, Virginia Fernandes; Fidelix, Tania; Santos, Laura; Lekwitch, Ilda; Soares, Simone; Gasparini, Andre; Augusto, Juliana
Abstract : Introduction: Primary Sjögren's syndrome (SSp) is a systemic autoimmune disease concerning the exocrine glands and internal organs. Therapeutic options mainly include symptomatic and supportive measures, whereas traditional immunosuppressive drugs have not presented efficacy in randomized trials. Abatacept is a T-cell co-stimulation modulator and there are evidences that this drug may be effective for treating Pss. Objectives: The objective of this trial was to evaluate effectiveness and safety of abatacept for 24 months in the treatment of pSS. Methods: Observational prospective study for 24 months. It was included 11 patients that filled the American-European Consensus criteria (2002). Patients received abatacept according the weight < than 60 kilos (500mg), 60 kilos to 100 kilos (750 mg) per month for 24 months. It was evaluated Sjögren's syndrome disease activity index (ESSDAI), salivary flow with no stimulation for 15 minutes, Schimer's ophthalmologic evaluation tests, Ocular Staining Score (OSS) e Break up time, quality of life by Medical Outcome Survey Short Form 36 (SF-36) and fatigue by FACIT Fatigue - The Functional Assessment of Chronic Illness Therapy. For statistical analysis was used the Wilcoxon's test for related samples and test T of Student to paired samples. The significance level of 5% was adopted and analyzes were accomplished in the R program (version 3.5.1). Results: This study was constituted from 11 women between the ages 25 to 81 years (average: 53.73 ± 15.07 years), being the majority afro-descendant women (54.5%). Of this total, 90.9% presented positive antinuclear antibody (ANA), 81.8% positive anti/SSA, and 90.9% positive rheumatoid factor. In relation to ESSDAI, 81.8% of the participants presented scores greater than 5. There was a statistically significant reduction in the ESSDAI IC 2.99 [-0.49; 7.99] (p = 0.013). Between the sub items of the ESSDAI, the ones that demonstrated the greatest modifications were articular and glandular. There was a significant increase in the salivary flow of the participants (dif = -0.90; IC-95%: -1.50; -0.50] after 24 months of treatment. There was no statistical difference between the beginning and after 24 months of treatment in the different evaluations, Schimer's ophthalmologic right eye IC 2.26 [-3.50; 12.5] p=0.423, Break up time OD 0.50 [-1.00; 2.49] p=0.307, OSS right eye IC: 0.50 [-2.50; 5.50] p=0.721. In the SF36 only in the Limitation for Emotional Aspects sub scale reported significant improvement (dif = 36.4; IC95%: -67.1; -5.57; p = 0.025), and FACIT presented no evidences of significant changes between pre and post treatment p = 0.356. Conclusion: The study demonstrates limitations due to the few number of patients included and for being an open study not controlled, but we observed a statistically significant reduction in the ESSDAI, increase in the salivary flow and in the sub scale Limitation for Emotional Aspects of the SF36, indicating a positive effect in the disease. References: [1] Clair E.W. ST. Sjögren's syndrome in: Gary S. Firestein MD, Ralph C. Budd MD, Sherine E. Gabriel MD MSc, et al.Kelley & Firestein's Textbook of Rheumatology, Tenth Edition. Elsevier 2017 73:1221-44. [2] Tsuboi H, Matsumoto I, Hagiwara S, et al. Effectiveness of abatacept for patients with Sjögren's syndrome associated with rheumatoid arthritis. An open label, multicenter, one-year, prospective study: ROSE (Rheumatoid Arthritis with Orencia Trial toward Sjögren's syndrome Endocrinopathy) trial. Mod Rheumatol 2016; 26(6):891-899 Disclosure of Interests: None declared